Pertanggung Jawaban Pidana Pengemudi dalam Keadaan Mabuk yang Menyebabkan Kematian - Paneo, Rahmat; Moonti, Roy Marthen; Ahmad, Ibrahim (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Crimes committed by drunk drivers that cause death are serious legal problems that have a broad impact on public safety. This study analyzes the form of criminal liability for such acts within the framework of Indonesian criminal law, by examining the application of the concepts of dolus eventualis and culpa. Although statutory provisions such as Articles 310 and 311 of the Traffic and Transportation Law and Article 359 of the Criminal Code have regulated criminal sanctions, implementation in the field is often weak and disproportionate. The legal approach tends to consider the act as negligence, whereas there is an element of conditional intent that must be considered. This study emphasizes the need for criminal law reform, strengthening law enforcement institutions, and public education to create a deterrent effect and protect people's right to life. The concept of dolus eventualis is an important alternative to expand criminal liability fairly and contextually.